The Development of Obesity Begins at an Early Age in Captive Common Marmosets (Callithrix jacchus) - POWER, MICHAEL L.; ROSS, CORINNA N.; SCHULKIN, JAY; TARDIF, SUZETTE D. (American journal of primatology, 2012)
Animal models to study the causes and consequences of obesity during infancy in humans would be valuable. In this study, we examine the patterns of fat mass gain from birth to 12 months in common marmosets (Callithrix jacchus). Lean and fat mass was measured by quantitative magnetic resonance at 1, 2, 6, and 12 months for 31 marmosets, 15 considered Normal and 16 considered Fat (>14% body fat) at 12 months. Animals were fed either the regular colony diet mix or a high‐fat variation. Subjects classified as Fat at 12 months already had greater lean mass (198.4 ± 6.2 g vs. 174.0 ± 6.8 g, P = 0.013) and fat mass (45.5 ± 5.0 g vs. 24.9 ± 3.4 g, P = .002) by 6 months. Body mass did not differ between groups prior to 6 months, however, by 1 month, Fat infants had greater percent body fat. Percent body fat decreased between 1 and 12 months in Normal subjects; in Fat subjects, it increased. The high‐fat diet was associated with body fat >14% at 6 months (P = 0.049), but not at 12 months. This shift was due to three subjects on the normal diet changing from Normal to Fat between 6 and 12 months. Although maternal prepregnancy adiposity did not differ, overall, between Normal and Fat subjects, the subjects Normal at 6 and Fat at 12 months all had Fat mothers. Therefore, diet and maternal obesity appear to have potentially independent effects that may also vary with developmental age. Although birth weight did not differ between groups, it was associated with fat mass gain from 1 to 6 months in animals with >14% body fat at 6 months of age (r = 0.612, P = 0.026); but not in 6‐month‐old animals with <14% body fat (r = –0.012, P = 0.964). Excess adiposity in captive marmosets develops by 1 month. Birth weight is associated with adiposity in animals vulnerable to obesity.